'Milih Dino' Culture in Pringapus Trenggalek and its Impact on Individual Psychology: Budaya ‘Milih Dino’ di Pringapus Trenggalek dan Dampaknya pada Psikologis Individu - Risky , Achamad; Himmatul , Firda; Dwi , Ristanti; Mahestika , Vanessa; Susilo, Joko (Procedia of Social Sciences and Humanities, 2024)
Choosing the right day and month in Javanese culture is a meaningful tradition, full of cultural values ​​and beliefs passed down from generation to generation. This tradition not only serves as a guide for determining the time for important events such as weddings, circumcisions and other ceremonies, but also helps build the cultural identity of the Javanese people. This article discusses the origins, methods, and benefits of this tradition and how it has been preserved in the modern era. Additionally, this article also looks at how the "choose the dino" tradition can affect the psychological aspects of the individuals involved. This research was conducted qualitatively using interview methods and literature study. Through in-depth observations and interviews with community leaders and Javanese tradition experts, it was found that choosing a good day aims to ensure smooth and safe running of important events. This article uses Conformity theory and Vygotsky's developmental theory to understand the psychological and social impact of these traditions, showing how social interactions and inherited cultural values can strengthen cultural identity.